1986
DOI: 10.1038/bjc.1986.43
|View full text |Cite
|
Sign up to set email alerts
|

Cell uptake, distribution and response to aluminium chloro sulphonated phthalocyanine, a potential anti-tumour photosensitizer

Abstract: Summary The uptake, retention and effects of aluminium chloro sulphonated phthalocyanine (AlSPc) were measured in two cell lines, UV-2237 a murine fibrosarcoma and the non-tumorigenic NIH/3T3 fibroblast line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 22 publications
4
53
0
Order By: Relevance
“…Therefore we have been investigating a new group of sensitisers, the phthalocyanines. Chloro aluminium sulphonated phthalocyanine (AlSPc) has been shown to be effective at sensitising the destruction of cells in culture Chan et al, 1986). We have shown that AlSPc is a more effective sensitiser than HpD for the treatment of the liver and a subcutaneous transplanted fibrosarcoma in the rat Tralau et al, 1987).…”
mentioning
confidence: 86%
“…Therefore we have been investigating a new group of sensitisers, the phthalocyanines. Chloro aluminium sulphonated phthalocyanine (AlSPc) has been shown to be effective at sensitising the destruction of cells in culture Chan et al, 1986). We have shown that AlSPc is a more effective sensitiser than HpD for the treatment of the liver and a subcutaneous transplanted fibrosarcoma in the rat Tralau et al, 1987).…”
mentioning
confidence: 86%
“…The emission spectra of this source has been documented elsewhere (Chan et al, 1986 The procedure used to establish AlSnPc-mediated cytotoxicity against WiDr cultures was similar to that described previously for PII (West, 1989 (Chan et al, 1990). …”
Section: Tumour Cellsmentioning
confidence: 99%
“…Generally, the active MPc contain central diamagnetic metal ions, such as aluminium, gallium, tin and zinc (Brasseur et al, 1985;Ben-Hur & Rosenthal, 1986;Brasseur et al, 1987;Chan et al, 1987aChan et al, , 1988Brasseur et al, 1988;Paquette et al, 1988) while sulphonation of the benzene rings of the macrocycle leads to solubility in water which facilitates administration to animals. One such compound, AlSPc, has been shown by ourselves (Chan et al, 1986(Chan et al, , 1988 and others (Sandeman et al, 1987;Tralau et al, 1987a;Nelson et al, 1988) to be a particularly promising agent for PDT. This substance possesses good tumour-localising capacity (Tralau et al, 1987a(Tralau et al, , 1987bChan et al, 1988Chan et al, , 1989 and causes substantial damage to a range of tumours of diverse histological origin (Sandeman et al, 1987;Tralau et al, 1987a;Chan et al, 1988;Nelson et al, 1988) with prolongation of survival times in treated animals (Chan et al, 1987b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ALSPc has the advantage that it is easily synthetised in reproducible form (a solution containing an average of three sulphonic acid groups per molecule). It is an effective photosensitiser both in vitro and in vivo and it has a single strong absorption peak in the visible spectrum at 675 nm (Chan et al, 1986). Outbred mice, weighing between 20-30 g were used for the normal studies and results compared with studies on the VMDk murine glioma model.…”
mentioning
confidence: 99%